Towards a Conceptual Understanding of the Transformation from Ritual to Theatre - Morgan, William; Brask, Per (Anthropologica, 2022)
Anthropologists and theatre historians have long posited a generic and historical relationship between ritual and theatre. This paper proposes that the emergence of theatre in state level societies may be understood by viewing the functions of theatre as adaptive transformations of the social control and integration functions characteristic of communal rituals in non-state societies. The proposition is tested against data concerning the sociopolitical circumstances surrounding the appearance of theatre in the newly emerged states of Ancient Greece and of Aztec Mexico.